Efektivitas Interprofessional Education Terhadap Pengembangan Kompetensi Kolaboratif Mahasiswa Kesehatan: Literature Review - Siti Zahara Nasution; Nur Hanifah; Evi Karota Bukit; Rika Endah Nurhidayah (STIKES Columbia Asia Medan, 2026)
Background: The increasing complexity of modern healthcare systems necessitates effective collaboration among healthcare professionals to ensure high-quality, safe, and patient-centered care. In this context, Interprofessional Education (IPE) has emerged as a strategic educational approach aimed at preparing healthcare students with the collaborative competencies required for interprofessional practice. Although numerous studies have reported the benefits of IPE implementation, a comprehensive review is needed to synthesize current evidence regarding its effectiveness in developing collaborative competencies among healthcare students. Objective: This literature review aimed to analyze and synthesize recent evidence on the effectiveness of Interprofessional Education in enhancing collaborative competencies among healthcare students. Methods: This study employed a descriptive literature review approach. Articles were retrieved from Google Scholar, PubMed, ScienceDirect, BMC, and JPKI databases using keywords related to Interprofessional Education, Interprofessional Collaboration, collaborative competence, interprofessional communication, teamwork, and patient-centered care. Article selection followed the PRISMA guidelines. Inclusion criteria included full-text articles published between 2021 and 2025 that examined the implementation of IPE or IPC among healthcare students or healthcare professionals. Of the 100 articles initially identified, 10 studies met the eligibility criteria and were included in the final analysis. Results: The findings demonstrated that the implementation of IPE significantly contributed to improving students’ readiness for interprofessional collaboration, interprofessional communication skills, teamwork effectiveness, understanding of professional roles and responsibilities, and overall collaborative competencies. Furthermore, IPE was found to enhance clinical skills and support the delivery of patient-centered care. However, the effectiveness of IPE implementation was influenced by several factors, including organizational culture, professional stereotypes, hierarchical structures, curriculum readiness, and institutional support within educational and healthcare settings. Conclusion: Interprofessional Education is an effective educational approach for fostering collaborative competencies among healthcare students. Therefore, the systematic, structured, and sustainable integration of IPE into healthcare education curricula is essential to prepare future healthcare professionals who can work collaboratively, improve healthcare quality, and contribute to safe, patient-centered care.